The wrong victim ebook - Brennan, Allison (Quinn & Costa, 2022)
From New York Times bestselling author Allison Brennan comes a gripping new thriller. A lethal attack with no clear motive...and a killer dead-set on keeping the truth buried. A bomb explodes on a sunset charter cruise out of Friday Harbor at the height of tourist season and kills everyone on board. Now this fishing and boating community is in shock and asking who would commit such a heinous crime—the largest act of mass murder in the history of the San Juan Islands. Was the explosion an act of domestic terrorism, or was one of the dead the primary target? That is the first question Special Agent Matt Costa, Detective Kara Quinn and the rest of the FBI team need to answer, but they have few clues and no witnesses. Accused of putting profits before people after leaking fuel endangered an environmentally sensitive preserve, the West End Charter company may itself have been the target. As Matt and his team get closer to answers, they find one of their own caught in the crosshairs of a determined killer. Don't miss THE MISSING WITNESS , the brand-new page-turning thriller from New York Times bestselling author Allison Brennan! A Quinn & Costa Thriller Book 1: The Third to Die Book 2: Tell No Lies Book 3: The Wrong Victim Book 4: Seven Girls Gone Book 5: The Missing Witness